Unravelling the sleep crisis: insomnia among medical students in government and private medical college students in Mysuru district - M., Rakesh; D., Sunil Kumar; Khan, Mudassir; Nath, Anchu R.; M., Sana Khader; P., Anila (International Journal Of Community Medicine And Public Health, 2024)
Background: Insomnia, a prevalent sleep disorder, significantly impacts medical students due to the high levels of stress and demanding academic schedules. The educational environment of medical students, marked by intense competition and high expectations, often contributes to chronic stress, a known precursor to sleep disturbances. This study aimed to compare the prevalence of insomnia among medical students in government and private medical colleges and assess the factors contributing to insomnia in these groups. Methods: The cross-sectional study was conducted among 490 medical students from government and private medical colleges over three months (April to June 2024). Systematic sampling was used to select participants, and data were collected via a self-administered questionnaire, including sociodemographic information and the Athens insomnia scale. Data were analysed using SPSS Version 26.0, with chi-square tests for qualitative data and Mann-Whitney U tests for insomnia comparisons. Results: The study revealed a significantly higher prevalence of insomnia in private medical college students (40.8%) compared to government college students (11.8%). Significant associations were found between insomnia and insufficient sleep, stress, and depression in both groups. Additionally, the use of mobile devices at night and irregular sleep patterns during exams were linked to higher insomnia rates. The median insomnia score was higher in private medical college students compared to government college students, indicating a statistically significant difference (p value <0.05). Conclusions: Targeted interventions to improve sleep quality and mental health support are crucial for this population. Regular assessments and feedback mechanisms should be implemented to enhance the effectiveness of these interventions.